REPETISI MOTIF FLORA DAN FAUNA PADA ELEMEN DEKORATIF DINDING FUNCTION HALL KASTUBA RESORT, LEMBANG - Celine Rei; Augustina Ika Widyani (PROSIDING SERINA, 2021)
The increasing number of visitors to Bandung becomes the starting point to re-evaluate the area’s accomodation facilities and services. It is important that a vacation space can help provide maximum assistance and comfort for the guests while at the same time are able to leave a good impression. Kastuba Resort is one of the leading mountain resort at Lembang. One way that can be done to fulfill the need is to design the space whilist implementing decorative elements to the chosen area which is Function Hall. Aside from the ability to gain interest from citizens, it can also give a deeper meaning and sense to the visitors of Kastuba Resort. The methods that is taken to achieve the final result are gathering datas, site observation, processing all the collected informations and drawing sketches. The decorative element was mostly inspired by Sundanese culture and tying it with Kastuba Resort image. The design holds on to the concept of natural, exoticness, traditional, open and exclusive. A final result that creates oneness is achieved by combining Sundanese artistic side which is peacock dance and Kastuba Resort logo itself. Resulting in a design that is unique and authentic. Message that wants to be delivered to the audience is the hope that each individual can be reminded to embrace their own uniqueness like how the peacock embraces its beauty in nature. Whilist the Kastuba flower not only used to exentuate Kastuba Resort image, but also as a reminder to appreciate the beauty of nature. Terjadinya peningkatan jumlah pengunjung ke Lembang sebagai salah satu daerah wisata di kota Bandung, menuntut adanya peningkatan fasilitas dan layanan tempat penginapan agar dapat mengakomodir kebutuhan pengunjung secara maksimal. Kastuba Resort merupakan salah satu tempat penginapan pegunungan terbaik yang terletak di Lembang. Upaya yang dilakukan untuk mewujudkan kebutuhan adalah dengan perubahan rancangan interior dengan penerapan elemen dekoratif pada ruang terpilih yaitu Function Hall. Penerapan elemen dekoratif selain dapat meningkatkan ketertarikan masyarakat untuk berkunjung ke tempat penginapan, dapat memperkuat citra penginapan sehingga memberikan kesan mendalam bagi pengunjung Kastuba Resort. Metode yang dilalui sebelum mencapai hasil akhir adalah pengumpulan data kualitatif yang diikuti dengan observasi lokasi, melakukan pengolahan ide-ide serta sketsa-sketsa. Pengolahan motif elemen dekoratif terinspirasi dari kebudayaan Sunda yang merupakan kebudayaan masyarakat setempat Lembang serta mengikatkannya dengan citra Kastuba Resort. Konsep perancangan yang ingin diterapkan adalah natural, eksotis, tradisional, terbuka dan ekslusif. Motif yang mengikat kesenian budaya Sunda yang terinspirasi dari tarian merak Sunda dan logo Kastuba Resort menghasilkan sebuah karya yang unik dan otentik. Makna yang ingin disampaikan adalah agar para individu mengingat bahwa setiap manusia memiliki keunikan mereka masing-masing yang patut dibanggakan, serta adanya logo Kastuba selain untuk menekankan citra Kastuba Resort tetapi juga sebagai upaya untuk menghargai alam sekitar.